A comprehensive comparative analysis of treatment modalities for sinonasal malignancies. Issue 16 (3rd April 2017) - Robin, Tyler P.; Jones, Bernard L.; Gordon, Oren M.; Phan, Andy; Abbott, Diana; McDermott, Jessica D.; Goddard, Julie A.; Raben, David; Lanning, Ryan M.; Karam, Sana D.
Abstract : BACKGROUND: Sinonasal malignancies are a rare and heterogeneous group of tumors for which there is a paucity of robust data with which to guide management decisions. The authors used the National Cancer Data Base to better understand the presenting characteristics of these tumors and to compare outcomes by treatment modality. METHODS: The National Cancer Data Base was queried for sinonasal malignancies diagnosed between 2004 and 2012. Overall survival was assessed using multivariate analyses and propensity score matching. RESULTS: A total of 11, 160 patients were identified for the initial analysis. The majority were male, aged 40 to 69 years, with tumors of the nasal cavity or maxillary sinus. Squamous cell histology was most common. The majority of patients presented with advanced tumor stage but without locoregional lymph node or distant metastases. Treatment modalities were compared for squamous cell carcinomas. In multivariate analysis, compared with surgery alone, patients who received adjuvant radiotherapy (hazard ratio [HR], 0.658 [ P <.001]), adjuvant chemoradiotherapy (HR, 0.696 [ P  = .002]), or neoadjuvant therapy (HR, 0.656 [ P  = .007]) had improved overall survival. Patients who received radiotherapy alone (HR, 1.294 [ P  = .001]) or chemotherapy alone (HR, 1.834 [ P <.001]) had worse outcomes. These findings were validated in propensity score matching. It is important to note that neoadjuvant chemoradiotherapy was associated with achieving a negative surgical margin (odds ratio, 2.641 [ P  = .045]). CONCLUSIONS: Surgery is the mainstay of therapy for patients with sinonasal malignancies, but multimodality therapy is associated with improved overall survival. Cancer 2017;123:3040–49. © 2017 American Cancer Society . Abstract : In the current large cancer registry study, multimodality therapy appears to be associated with improved overall survival in patients with sinonasal cancers. This finding emphasizes the importance of shared multidisciplinary decision making in the management of these patients with this complex malignancy.